Diagnosing isolated hepatosplenic tuberculosis in an immunocompetent patient: a case report. (July 2018) - Dawani, Om; Khan, Raja Samir; Syed, Mujtaba Jamal; Shehzad, Abdul Moid; Alratoot, Ahmed; Ahmed, Muhammad Faizan
For many years, tuberculosis (TB) has been endemic in Pakistan; many rare and unusual presentations have been reported. There is a myriad of non-specific symptoms which always requires a high index of clinical suspicion for TB. World Health Organization data suggest that Pakistan ranks as the fifth highest country burdened with TB and has the fourth highest prevalence of multi-drug resistant TB globally. With an annual incidence of 277 cases per 100, 000, the importance of early diagnosis and treatment is self-evident. We present a case where a strong suspicion of isolated hepatosplenic TB in an immunocompetent patient justified a directed approach.